Filipina migrant domestic workers' identity and narrative practices on social media from self to nation - Bancoro, Sharon V.
In real life and on social media, Filipina migrant domestic workers are excluded from the construction of their own collective identity. This brings to the surface the voices of Filipina migrant domestic workers in this process of constructing their collective identity. The study, which uses constructivist grounded theory, draws data from the personal online narratives of five migrant tellers that were originally published on the Facebook page Definitely Filipino and its blog site of the same name. Transcripts of the researcher's personal interviews with the tellers and the comment section of Definitely Filipino are also analyzed. This study aims to conceptualize how these migrant storytellers are able to construct a positive collective identity through their narrative practices on social media and to theorize how this collective identity construction is implicated in the notions of the Filipino nation in global context.